Seismic behavior of exterior RC beam-column joints without code-specified ties in the joint core. (1st February 2021) - Pauletta, Margherita; Di Marco, Caterina; Frappa, Giada; Miani, Marco; Campione, Giuseppe; Russo, Gaetano
Highlights: Two identical full-scale exterior beam-column joints are built with a construction error. In comparison to DHC joints, some ties are lacking in the core of the considered joints. The performance of the joints under cyclic loads is tested. Due to the construction error, shear failure occurs in both joints. Pauletta et al. and Eurocode 8 provide reliable predictions of joint shear strength. Abstract: Beam-column joint design for reinforced concrete (RC) buildings is a critical issue for modern earthquake engineering, because for these structural elements, the current codes provide several geometrical constraints and reinforcement provisions, which may be very complex to implement during the construction phase. To investigate how a construction error might influence the joint behavior, two identical full-scale exterior beam-column joints specimens are built, according to Italian Building Code specifications for the high ductility class, but without the required horizontal ties inside the joint panel. This construction error could be plausible because, according to the design drawings, the panel was very crowded with reinforcement bars and the concrete casting and compaction was objectively difficult. The performance of the joints is tested under cyclic loads simulating seismic actions. Although the joints are designed for high ductility class, a 50% reduction of the horizontal reinforcement in the joint core, and 25% in the critical regions, led the specimens to shear failure, with crushing of the concrete in the joint core. A discussion of the failure mechanism is presented, in which shear strength obtained from the tests is compared to shear strengths calculated using the expressions provided for exterior joints by Eurocode 8, the ACI Code and the formula proposed by Pauletta et al.